2021
DOI: 10.2355/isijinternational.isijint-2020-768
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Particle Mixing Behavior in High Speed Shear Mixer and Cylinder Mixer

Abstract: The mixing effect of powder materials is crucial in the iron ore granulation process, which determines the composition and particle size distribution, thereby affecting the quality of the sinter. To study the mixing effect of powder particles in a high speed shear mixer (HSSM) and cylinder mixer (CM), numerical simulation based on discrete element method was adopted in this work. For the CM, the particle movement consists of slipping and slumping. For the HSSM, the particle movement consists of rolling and cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To improve the permeability of sinter packed bed for achieving efficient utilization of low-grade iron bearing minerals, extensive studies have been reported worldwide. The most effective way to obtain the desired permeability of a sinter packed bed is to enhance the granulation properties of the granules, which includes using an intensive mixing machine [5][6][7][8][9][10] and the addition of solid binder [11][12][13][14][15] in the granulation. In addition to this, the optimized moisture [16][17][18][19][20] and the implementation of pre-briquetting treatment [21] in the granulation process also improve granulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the permeability of sinter packed bed for achieving efficient utilization of low-grade iron bearing minerals, extensive studies have been reported worldwide. The most effective way to obtain the desired permeability of a sinter packed bed is to enhance the granulation properties of the granules, which includes using an intensive mixing machine [5][6][7][8][9][10] and the addition of solid binder [11][12][13][14][15] in the granulation. In addition to this, the optimized moisture [16][17][18][19][20] and the implementation of pre-briquetting treatment [21] in the granulation process also improve granulation performance.…”
Section: Introductionmentioning
confidence: 99%